3D printing concrete with recycled sand: The influence mechanism of extruded pore defects on constitutive relationship. (1st June 2023) - Liu, Chao; Wang, Zhihui; Wu, Yiwen; Liu, Huawei; Zhang, Tianguo; Wang, Xin; Zhang, Wei
Abstract: Recycled sand (RS) as an environmental-friendly building material, has shown great prospects for the digital construction of buildings. In this study, 3D printed recycled sand concrete (3DPRSC) mixed with RS was prepared, and the related compressive strength and constitutive relationships were investigated on different RS replacement ratios and construction methods. The geometric characteristics and spatial distribution of pore defects were analyzed by the combined X-CT and MIP, and the microscopic morphology of RS and natural sand was analyzed by SEM. The results showed that the compressive strength and constitutive curves have apparent anisotropic characteristics. With the increase in the RS replacement rate, the compressive strength tended to decrease. The ellipsoidal pore geometry's arrangement of 3DPRSC extruded pore defects differs in different printing directions, and the pore defect distribution characteristics vary with the accumulated height of the filaments and the printing direction. The mechanism of the formation and distribution of extruded pore defects on the compressive strength and constitutive relationship was analyzed, and a model of the constitutive curve based on extruded pore defects and anisotropy was established, which provided a theoretical basis for the nonlinear analysis of the engineering structure of 3DPRSC. Highlights: Testing the uniaxial compression of the specimens in different loading directions. The concrete pore structure in different recycled sand replacement ratios was tested. The anisotropic characteristics of the stress-strain curve were described. Proposing the constitutive equation of 3D printing concrete with recycled sand.